Global temporal trends and predictions in the burden of chronic kidney disease attributable to diet high in sugar-sweetened beverages: an age-period-cohort analysis for GBD 2021 - Ma, Sijia; Song, Shuxin; Tang, Hui; He, Fang-Fang (Frontiers in Endocrinology, 2025)
ObjectiveThis study aims to evaluate temporal trends in chronic kidney disease (CKD) mortality attributable to excessive sugar-sweetened beverage (SSB) intake globally from 1990 to 2021 and to forecast future trends until 2040.MethodsUtilizing the Global Burden of Disease (GBD) 2021 dataset, we focused on the temporal trends in SSB-related CKD mortality. An age-period-cohort (APC) model was employed to analyze mortality trends by age, period, and cohort.ResultsIn 2021, the deaths attributable to SSB-related CKD were particularly elevated in high and middle sociodemographic index (SDI) regions. Among the countries studied, 62 had at least one million deaths in 2021, with the USA, Mexico, China, India, and Brazil being the top five. From 1990 to 2021, the net drift of SSB-related CKD mortality ranged from 0.54% (95% UI: -0.72 to 1.81) in low SDI regions to 3.83% (95% UI: 3.40 to 4.27) in high SDI regions. Local drift estimates indicated elevated mortality across all age groups. Globally, the increasing mortality of SSB-related CKD shifted towards the older population. Age effects showed a similar trend across all SDI regions, and the risk increased with age. Period effects for low-middle, middle, high-middle, and high SDI regions showed an improving trend before 2004, but an adverse trend after 2004. Low-middle, middle, and high SDI regions showed unfavorable trends in successive cohorts. Projections indicate a continuous increase in global deaths from SSB-related CKD over the next two decades.ConclusionThis study is the first to investigate the global temporal trends in the burden of SSB-related CKD. Over the past three decades, mortality from SSB-related CKD has demonstrated a generally upward trajectory. Evidence-based public health interventions and policies targeting SSB consumption and CKD management are imperative in high-burden regions to mitigate the advancing impact of SSB-related CKD on public health.